Grande projeto agroflorestal Suzano e transformações na força de trabalho na cidade de Imperatriz, Maranhão, Brasil - Leal, Maria da Conceição Mesquita (2024)
This research aims to understand the transformations in the medium/technical level workforce in the city of Imperatriz, triggered by the implementation of the Suzano Papel e Celulose manufacturing unit. With the agroforestry projects came investments in infrastructure for the national integration of the extracted and transformed raw material. Thus, an enclave model was structured, centered on a frontier economy and based on the exploitation of resources according to an infinite logic. This not only deepens the role of peripheral regions such as Maranhão, in the uneven and combined development model, but also accentuates the role of the State, the reorganization, specialization and orientation of the region's workforce to meet the logical and full functioning of the chain pulp and paper production. The industrial base planted over time in the region adds to the general conditions of cheap land, transport infrastructure to the port of Itaqui, water resources, in addition to the presence of abundant labor, which allowed the implementation of Suzano in Imperatriz from 2008. The municipality of Imperatriz is part of the new eucalyptus plantation corridor, expanded in the last ten years by Suzano Papel e Celulose, and has been undergoing significant changes as a result of the modernization and specialization of the mechanized agroindustry on the agricultural frontier. Little was discussed about the adaptive process of the local and regional workforce, the dynamics and specialization of work in the productive chain of the pulp and paper industry linked to the Suzano factory in Maranhão. Within this logic of reconfiguration, industries, in order to produce in a modern way, call on other actors to participate in their actions. The State, subordinated to industrial activity in a new model of fiscal wars, offers exemptions at the expense of the exploitation of social and environmental resources in the name of the discourse of development and creation of jobs and income. The attraction space is thus subservient to the logic of production and starts to be reorganized based on its own dynamics that serves the company. It is up to the worker, within a dominant logic, to restructure, reorganize, modify and meet new demands in order to, from there, meet the requirements that follow in the market. Methodologically, in addition to reviewing the relevant literature, we used, together with field research, secondary data on changes in local employment and local professional recommendations arising from the implementation of Suzano. The collection of data from secondary sources forwarded to the websites, the Annual Social Information List (RAIS), the General Register of Employed and Unemployed People (CAGED), the Ministry of Labor and Employment (MTE) of the Program for the Dissemination of Labor Statistics (PDET), the Brazilian Tree Industry (IBÁ), the Brazilian Institute of Geography and Statistics (IBGE), the Food and Agriculture Organization (FAO), the Ministry of Development, Industry, Commerce and Services (MDIC), Catho Empresas, National Confederation of Industry (CNI), Securities and Exchange Commission (CVM), Bradesco Department of Research and Economic Studies (Depec/Bradesco), Ministry of Labor and Social Security (MTPS). In addition to these secondary data, data were obtained from Suzano Papel e Celulose reports and from local technical schools and universities. The research results point to a transformation of work, justifying the need to intensify reflections on the processes of (re)qualification and maintenance of the local workforce.